Electroencephalographic findings in patients with major depressive disorder during cognitive or emotional tasks: a systematic review - de Freitas,Sabrina B. (2016)
Objective: Major depressive disorder (MDD) is a prevalent psychiatric condition characterized by multiple symptoms that cause great distress. Uncovering the brain areas involved in MDD is essential for improving therapeutic strategies and predicting response to interventions. This systematic review discusses recent findings regarding cortical alterations in depressed patients during emotional or cognitive tasks, as measured by electroencephalography (EEG). Methods: A search of the MEDLINE/PubMed and Cochrane databases was carried out using the keywords EEG and depression, confined to article title. Results: The studies identified reveal the frontal cortex as an important brain structure involved in the complex neural processes associated with MDD. Findings point to disorganization of right-hemisphere activity and deficient cognitive processing in MDD. Depressed individuals tend to ruminate on negative information and respond with a pattern of relatively higher right frontal activity to emotional stimuli associated with withdrawal and isolation. Conclusion: Patients with MDD may have altered dynamic patterns of activity in several neuroanatomical structures, especially in prefrontal and limbic areas involved in affective regulation. Identification of these alterations might help predict the response of patients to different interventions more effectively and thus maximize the effects both of pharmacotherapeutic and of psychotherapeutic strategies.